Enhancing the antioxidant capacity of Fe single-atom nanozymes through local coordination manipulation for psoriasis treatment - Hongjin Xue; Yunqian Li; Xinyu Ma; Qi Zhang; Junkai Zhu; Xiaoli Ni; Jianfeng Qiu; Zhengjun Li; Zhen Mu (Materials Today Bio)
Psoriasis is a chronic skin condition with significant unmet medical needs, characterized by high levels of reactive oxygen species (ROS) and accompanying oxidative stress. In this study, we developed a novel single-atom iron nanozyme (Fe-N3), designed to mimic natural antioxidant enzymes, for the effective treatment of psoriasis. By optimizing the local coordination environment of Fe atoms, Fe-N3 demonstrated superior superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APx), and glutathione peroxidase (GPx)-like activities compared to Fe-N4. These properties enable efficient ROS scavenging and oxidative stress alleviation. Theoretical analyses revealed that Fe-N3 possesses lower energy barriers for ROS decomposition, explaining its superior catalytic performance. Furthermore, in vitro and in vivo experiments have demonstrated that Fe-N3 nanozyme exhibited remarkable therapeutic effects with extremely low cytotoxicity, effectively inhibiting pathological epidermal proliferation, downregulating key inflammatory factors, and reducing the expression levels of psoriasis-associated pathway proteins. This work highlights the promise of single-atom nanozymes in the curing of inflammatory skin diseases, advancing the transformative role of nanotechnology in biomedicine.